2019
DOI: 10.1016/j.eclinm.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of the SNAP 12-hour Acetylcysteine Regimen for the Treatment of Paracetamol Overdose

Abstract: Background Acetylcysteine (NAC) is effective at preventing liver injury after paracetamol overdose. The Scottish and Newcastle Anti-emetic Pre-treatment for Paracetamol Poisoning (SNAP) Study demonstrated that a 12 h NAC regimen was associated with fewer adverse drug reactions compared with the standard 21 h regimen. Here, we describe the clinical effectiveness of the SNAP NAC regimen. Methods The SNAP regimen, consisting of intravenous NAC 100 mg/kg over 2 h then 200 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 16 publications
2
53
0
3
Order By: Relevance
“…This included gastrointestinal, cutaneous and systemic reactions. Similarly, the SNAP regimen studies which decreased the infusion rate of the loading-dose over the first hour have shown similar findings [10,11]. Some previous studies assessing safety of the two-bag regimen did not find a difference in the incidence of gastrointestinal reactions [12,13], but in this larger efficacy study, these were significantly less frequent that with the three-bag regimen.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This included gastrointestinal, cutaneous and systemic reactions. Similarly, the SNAP regimen studies which decreased the infusion rate of the loading-dose over the first hour have shown similar findings [10,11]. Some previous studies assessing safety of the two-bag regimen did not find a difference in the incidence of gastrointestinal reactions [12,13], but in this larger efficacy study, these were significantly less frequent that with the three-bag regimen.…”
Section: Discussionsupporting
confidence: 66%
“…The incidence of peak INR >2.0 was 6.9% (n = 23) with the two-bag regimen vs 7.4% (n = 15) with the three-bag regimen (Difference: À0.5, 95% CI À5.1 to 3.9). The median time from paracetamol ingestion to start of acetylcysteine was 14 h (11,18) in the twobag group vs 13 h (11,17) in the three-bag group (p = 0.1). Fulminant hepatic failure developed in four patients (1.2%) receiving the twobag regimen and three patients (1.5%) receiving the three-bag regimen (Difference: À0.3, 95% CI À2.3 to 1.7).…”
Section: Acute Single Ingestions With Initial Blood Tests Performed 8mentioning
confidence: 90%
See 1 more Smart Citation
“…8 Although the recent SNAP study showed that for POD presenting to the emergency department, a new 12-hour 300 mg/kg NAC regimen was better tolerated and non-inferior to an older 21-hour regimen in terms of consequent hepatic injury and ALF, there is still a lack of clarity regarding the optimal duration of NAC infusion once ALF has developed. 9 Furthermore, caution is required in extrapolating the findings of this trial to delayed or staggered overdoses where outcomes tend to be worse.…”
Section: Initial Managementmentioning
confidence: 99%
“…17,18 Currently all patients deemed to need treatment receive the same dose of acetylcysteine, a practice which results in significant patient numbers being under or over treated. 19 can be included as a biomarker of hepatocellular injury in short--term rat toxicology studies and its use adds benefit in detecting hepatotoxicity in this species. 20 miR--122 is also a new biomarker for liver disease in dogs that is gaining traction in clinical veterinary practice.…”
Section: Uloq (Concentration Cv) 1578mentioning
confidence: 99%